The Pathogenic Role of Actinomyces spp. and Related Organisms in Genitourinary Infections: Discoveries in the New, Modern Diagnostic Era - Márió Gajdács; Edit Urbán (MDPI AG, 2020)
Actinomycosis is a chronic, suppurative, granulomatous infectious disease, caused by different species of Actinomyces bacteria. To date, 26 validly published Actinomyces species have been described as part of a normal human microbiota or from human clinical specimens. Due to the rapid spread of new, modern diagnostic procedures, 13 of 26 of these species have been described in this century and the Actinomycetaceae family has undergone several taxonomic revisions, including the introduction of many novel species termed Actinomyces-like organisms (ALOs). There is scarce data available on the role of these novel bacterial species in various infectious processes in human medicine. The aim of this review is to provide a comprehensive overview of Actinomyces and closely related organisms involved in human diseases-with a special focus on newly described species-in particular their role in genitourinary tract infections in females and males.